A Cross-sectional Study Evaluating Childhood Autism Awareness of Residents Otorhinolaryngology Department in Istanbul - LÜLECİ, NİMET EMEL (ISTANBUL TRAINING & RESEARCH HOSPITAL, 2019)
Introduction: Otorhinolaryngology (ENT) physicians may be effective in the early diagnosis of autism spectrum disorder (ASD). The aim of this study was to investigate the awareness of ENT residents in Istanbul about recognizing ASD. Methods: The type of the study was cross-sectional. The study population consisted of 97 ENT residents, and 83 (85%) of these residents were included in the study. The questionnaire consisted of questions about the sociodemographic data of the participants and Autism Spectrum Disorder Awareness Questionnaire. Autism Spectrum Disorder Awareness Questionnaire contains the findings of ASD reported in the literature. This questionnaire includes observable findings of possible ASD in a child during routine examination of the ENT physician. Results: In our study, the most known finding of childhood autism was found to be difficulty in making eye contact (97.5%). Regarding work experience, difficulty in making eye contact (100%) and lack of age-appropriate language development (91.5%) findings were well-known findings among residents with less than four years of experience. On the other hand, very sensitive vision, hearing and touch senses (95.8%) and seem unable to hear even if hearing tests are normal (91.7%) findings were more prominent among residents with four or more years of experience. Conclusion: The ASD awareness of the ENT residents participating in our study can be considered as relatively good. The Autism Spectrum Disorder Awareness Questionnaire developed by the researchers is planned to be validated with the studies to be carried out later and developed to be used for ENT specialists. Such questionnaires can also be used to raise awareness among ENT residents and specialists.
Keywords: Awareness; childhood autism; otorhinolaryngology; resident; Turkey; SPECTRUM DISORDER; KNOWLEDGE; CHECKLIST; TODDLERS; ATTITUDE